Hukum Jaminan dalam Pembiayaan Modal Kerja (Akad Muḍārabah) di Bank Syariah dalam Pendekatan Maqāṣid Syarī’ah - Waldi Nopriansyah; Abdul Mujib; Ali Sodiqin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study aims to determine the law of guarantees in working capital financing (muḍārabah contracts) in Islamic banks from the perspective of maqāṣid syarī’ah. This type of research is qualitative research that is literary. The approach in this study uses the sharia maqāṣid system. The results of the study show that the guarantee applied by Islamic banks to working capital financing contracts (muḍārabah contracts) is a must that must be carried out by the bank in implementing the precautionary principle. While the maqāṣid sharia view, the application of guarantees carried out by Islamic banks in financing working capital specifically to secure the assets of ṣāḥib al-māl (hifẓ al-māl), and in general the guarantee law has entered into the elements of daruriyat al-khamsah, namely hifẓ al-dīn, hifẓ al-nafs, hifẓ al-‘aql, hifẓ al-nasl dan hifẓ al-māl. Therefore, applying the guarantee law is permissible to protect the assets of ṣāḥib al-māl.